Intraneural Pseudoperineuriomatous Proliferations and Traumatic Neuromas: A Retrospective Multicenter Study of Clinicopathological Characteristics - Gundlach, Jully Elisabeth [UNESP]; Montalli, Victor Angelo Martins; Agatti, Larissa Araujo; Abrantes, Thamiris Castro; Bezerra, Kelly Tambasco; Abrahão, Aline Corrêa; Romañach, Mário José; Oliveira, Silvio Luiz Vieira; Almeida, Nara Ligia Martins; Lara, Vanessa Soares; Felix, Fernanda Aragão; Caldeira, Patrícia Carlos; et al. (Springer Nature, 2025)
Background and Purpose: Described in 2013, intraneural pseudoperineuriomatous proliferations (IPP) present perineurial cells concentrically surrounding the axon-Schwann cell complexes, forming pseudo-onion bulbs. Different from intraneural perineuriomas, rare neoplasms with differentiation of perineural cells, IPP are reactive, associated with fibrosis, and frequently diagnosed histologically as traumatic neuroma (TN). The aim of this study was to characterize IPP by exploring its clinicopathological features and differentiating it from the main neural lesions that are part of the histopathological differential diagnosis through a retrospective study in six Brazilian Oral Pathology laboratories. Methods: Cases diagnosed as IPP, TN and intraneural perineuriomas were selected from the archives of the participating centers. Data on age, sex, race, symptoms, site, size, and clinical features and diagnosis were obtained from histopathological reports. Hematoxylin and eosin-stained slides were then re-evaluated by two examiners. Finally, statistical tests were performed to assess the association between clinical, pathological and demographic characteristics (p < 0.05). Results: After reclassification, 152 TN, 48 IPP and no case of intraneural perineurioma were diagnosed. Clinically, IPP and TN are similar, but IPP affects younger individuals, presents less reported pain, and is more commonly found on the tongue, while TN is frequently observed on the lip, alveolar ridge, and mental foramen. Both lesions typically present as fibrous nodules, often clinically misdiagnosed as fibrous hyperplasia. IPP is fibrous in all cases, more superficial in the mucosa, less frequently associated with adipose tissue and inflammation. These features may assist clinical dentists and pathologists in differentiating lesions. Conclusion: Although histologically similar, pathologists should note the perineural cell proliferation in IPP to avoid confusion with TN (a common reactive lesion) or intraneural perineurioma (a rare neoplastic lesion).
Keywords: GLUT-1 protein; Nerve sheath neoplasms; Perineurioma; Pseudoperineurioma; Traumatic neuroma